Low Pass Filter Design With Artificial Ground Structure - Wahyu Hendra Gunawan; Fitri Oktafiani; Bambang Sugeng; Lukman Lukman (JST (Jurnal Sains Terapan), 2017)
In this paper, low pass band filter with via holes and using artificial ground structure are proposed. The design contains a u-shaped parasite element and gives via hole which is connected to the ground on the adjacent side with a copper. A hole in this design has a diameter 1 mm. The A have the form square 15mm x 17.5mm, given an effect, if compared with the non-artificial ground structure system, this addition show that the bandwidth of the low pass filter is shifting regarding this condition with value 400Mhz at frequency 1GHz.On this paper, the low pass filter also gives the pass band filter on frequency 3.2GHz which is constructed by the artificial ground structure. The simulation results with this design are simulated by computer based on finite integration method and show a good agreement and can be performed for a low pass band filter applications in the future. Keywords: low pass filter, less via, artificial ground structure